คุณภาพชีวิตการทำงานกับความผูกพันต่อองค์การของบุคลากรสวนสัตว์เชียงใหม่ - แก้วกาญจน์ วิชัยรัตน์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This research had the objectives of studying the relationship between personal factors and the quality of working life of Chiang Mai Zoo personnel as well as their engagement with the organization. The research population was 282 personnel of Chiang Mai Zoo and the tool used was a questionnaire related to personal factors, quality of working life and organizational engagement of the sample group. The data was analyzed using frequency, percentage, mean and standard deviation whereas the significance was tested using the T-test, the F-test and Person’s Product Moment Correlative Coefficient. The findings were that the Chiang Mai Zoo personnel indicated their overall opinions about the quality of working life to be at a moderate level and the three aspects in this category that were ranked at a high level were social contribution, career advancement and security as well as the rhythm of life. The five aspects ranked at a moderate level were personal rights in the work place, opportunities to use and develop personal capabilities, cooperation and relationship with other people, work safety and health promotion as well as fair and sufficient remuneration. Differences in personal factors of the personnel of Chiang Mai Zoo could affect their quality of working to a certain extent. In this light it was found that their age, salary and work division caused their quality of working to vary. Regarding organizational engagement, the Chiang Mai Zoo personnel rated all three aspects at an high level respectively as follows: willingness to do their best for the benefit of the organization, the desire to remain members of the organization along with their confidence and acceptance of the goals and values of the organization. Differences in personal factors that would affect the organizational engagement of the Chiang Mai Zoo were factors concerning their age, marital status, work division and duration of the term of work. Regarding the quality of working life of the personnel of Chiang Mai Zoo in general, it was found that it had a positive relationship with the organizational engagement at a moderate level.